Highly sensitive sensor based on NaBi(MoO4)2/MWCNT composites. (26th September 2018) - Zhu, Chunhua; Du, Feipeng; Fu, Ping; Wang, Shenggao; Lin, Zhidong
Abstract: The n-type semiconductor sodium bismuth molybdate and p-type multiwall carbon nanotube (n-NaBi(MoO4 )2 /p-MWCNT) composites were synthesized by solvothermal method. MWCNT were added to the mixed solution of NaBi(MoO4 )2 precursor before solvothermal. All the as-prepared NaBi(MoO4 )2 were the same tetragonal scheelite nanocrystal, the composites have similar specific surface area and higher than pure NaBi(MoO4 )2 . SEM results showed that the composites were composed of NaBi(MoO4 )2 nanoparticles coated MWCNT, the morphology of the NaBi(MoO4 )2 in composites was nanoparticles and different from nanorods in the pure NaBi(MoO4 )2 . The low MWCNT content composites show good gas sensitivity. The sensors based on 1 wt% MWCNT doping NaBi(MoO4 )2 shows the highest gas response and selectivity to n-butanol at 300 °C. The 1 wt% MWCNT doping NaBi(MoO4 ) sensor can be appiled as n-butanol gas sensors.